The Dilemmas Regarding Imbalances in Globalization Processes - Jolanta ZIEZIULA (Communications of International Proceedings, 2020)
Globalization is probably one of the most commonly used words to describe the modern world in the last thirty years. However, the protests of the opponents of globalization are becoming increasingly frequent. What is this happening? The aim of this paper is to depict the negative phenomena associated with the development of globalization processes which contribute to the general imbalance of global growth processes and prevent sustainable world development. An attempt has been made to identify the conditions which need to be met to achieve optimum or at least sufficient balance. The analysis investigates the four principal spheres of globalization processes: economic, institutional, social and natural. The dialectical method was adopted to analyze the phenomena. The research was carried out using cause and effect, induction and deduction methods. The paper was based on the generally available, extensive source literature. The study carried out demonstrates that each of the spheres mentioned above remains in a great imbalance which prevents the achievement of an overall equilibrium. It is, therefore, necessary to take action to restore partial equilibria and then (or at the same time) coordinate the different components in order to create an overall equilibrium – integrated governance.
Keywords: Globalization; Equilibrium; Development.